Assessment of Role of Human Papilloma Virus in Patients with Oral Squamous Cell Carcinoma - Tyagi, Krishan Kumar; Pradhan, Megha; Grewal, Rajbir Kaur; Sherchan, Prabesh; Pasha, KSA (Journal of College of Medical Sciences-Nepal, 2019)
Background: Head and neck malignancies include malignancies instigating in the oral cavity, the orophar-ynx, the hypopharynx and the larynx. We planned the present study to assess the role of human papilloma virus (HPV) in patients with oral squamous cell carcinoma (OSCC). Methods: The present study included assessment of role of human papilloma virus in patients with oral squamous cell carcinoma. A total of 50 histopathologic proven cases of well differentiated OSCC were included in the present study. A total of 50 healthy oral mucosal tissues (controls) were also included in the present study. The controls were obtained while surgical removing the impacted teeth. DNA was obtained from the tissue sections and underwent Polymerization chain reaction for identification of HPV 16/18. All the results were summarized in Microsoft excel sheet and were analyzed by SPSS software. Results: HPV was absent in all the cases of control group, whereas among the OSCC group, the HPV was detected in 46 percent of the cases. In the remaining 54 per-cent of the cases of the OSCC group, HPV was absent. Significant results were obtained while comparing the presence of HPV in between the OSCC group and the control group. Conclusions: HPV was present in sig-nificant number of OSCC cases. Therefore; HPV might play a contributing role in the etio-pathogenesis of OSCC.